The Fulfillment of Rights to Citizenship for Migrant Worker Deportees in Nunukan District - Mahfud, Muh. Afif; Wibawa, Kadek Cahya Susila; ALW, Lita Tyesta; Saraswati, Retno (LAW REFORM, 2022)
Rights to Citizenship must be protected because it is the basis to be able to access the other rights. Rights to citizenship of migrant workers in Nunukan District is potentially expired and lost if they do not renew their passports. The same case may occur with illegal migrant workers who stay for 5 years abroad. This article aims to analyze the potential of stateless person in Nunukan District, the effort made by the government to handle the issue, and the ideal construction of legal protection for stateless person. This study applied socio legal approach using primary and secondary data which were collected through interview, observation, and in depth interview. Those data then were analyzed qualitatively. Based on the analysis, it is concluded that: (1) the potential of being stateless person in Nunukan District occurred in migrant workers whose passports were expired for more than 5 years, irregular migrant workers who stayed abroad for more than five years, the descendants or children of migrant workers who were born and were raised in Malaysia; (2) the government prevents the occurrence of stateless person: (a) integrated management of handling migrant workers; (b) sweeping in order to prevent irregular migrant workers; (c) simplifying the issuance of Letter of Arrival of Indonesian Citizen (SKDWNI) and Letter of Overseas Arrival (SKDLN); (3)ideal construction of the protection of right to citizenship  for migrant workers is the extension of the scope of migrant workers protection agreement, and the placement of Citizenship and Civil Record Agency officers in order to make the paperwork handling of citizenship document easier.